2015
DOI: 10.1080/17457300.2015.1032978
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of childhood poisoning in the home: overview of systematic reviews and a systematic review of primary studies

Abstract: Unintentional poisoning is a significant child public health problem. This systematic overview of reviews, supplemented with a systematic review of recently published primary studies synthesizes evidence on non-legislative interventions to reduce childhood poisonings in the home with particular reference to interventions that could be implemented by Children's Centres in England or community health or social care services in other high income countries. Thirteen systematic reviews, two meta-analyses and 47 pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 56 publications
1
22
0
1
Order By: Relevance
“…For the NMAs, data on the effectiveness of poison prevention interventions was extracted from primary studies identified in 2 newly-undertaken systematic reviews: a systematic review of reviews [ 15 ] and a systematic review of primary studies published since the most comprehensive systematic review [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…For the NMAs, data on the effectiveness of poison prevention interventions was extracted from primary studies identified in 2 newly-undertaken systematic reviews: a systematic review of reviews [ 15 ] and a systematic review of primary studies published since the most comprehensive systematic review [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…12,13 According to WHO report 2 effective interventions in reducing poisoning should involve, in addition to the exclusion of toxic substances, broader strategies that encompasses the legal obligation of adopting embalagens especiais para crianças (EEPC) (seal proof packages for children) and packaging and marketing with non-lethal doses. 2,14 Also according to this report, the use of keys in cabinets and drawers are effective practices for prevention. There is no sufficient scientific evidence proving that guidance to parents/children and actions of good matters at home reduce poisoning in childhood.…”
Section: Discussionmentioning
confidence: 99%
“…1 Among 15-to 19-year-olds, it represented the 13th cause of death worldwide in 2014. 1 Moreover, poisoning leads to a substantial number of hospitalizations 2 .…”
Section: Introductionmentioning
confidence: 99%